The view of the Clinical Obstetrician in the Caesarian vs. Normal Childbirth Controversy - Camano, Luiz; de Souza, Eduardo (O Mundo da Saúde, 2017)
Obstetrics has not been indifferent to the profound socioeconomic and cultural changes, nor to the scientific technological achievements of the last decades. Obviously, it also had to adjust, adapt and evolve in relation to this new vision. Changes in the obstetric population have also occurred. Women have stopped getting pregnant in their nubility. They first seek professional and economic achievement and then think about childbearing. The number of elderly and late primigravidae has grown; often, from assisted reproduction. Pregnant women have conquered the right of being better assisted and the respect regarding their convictions. We have seen and read concerning the emphasis with which women, who desire a normal birth, receive support and encouragement. Whereas other women, convicted in their decision to receive their child through cesarean, do not receive the same consideration.